(untitled) (Research, Society and Development, 2022)
Objective: to describe the scenario of mortality of children under five years of age, due to preventable causes, living in Brazilian regions, between 2010 and 2019. Methodology: this is an ecological study that used the List of Causes of Preventable Deaths by Interventions of the Unified Health System (SUS) and official secondary data from the Ministry of Health. The Infant Mortality Rate (TMIN) and TMIN were calculated due to preventable causes, proportional avoidable mortality by regions and groups of causes, in addition to identifying the sociodemographic characteristics of pregnant women and newborns from the regions of Brazil, comparing the first five-year period of the decade with the second. Results: of the 439,204 deaths of children in childhood, 65.3% were preventable. Despite the fall in TMIN and TMIN due to preventable causes in all regions, they present heterogeneous distribution in Brazil. Deaths reduced by adequate ’attention to women during pregnancy’ showed the highest predominance of deaths in childhood and more than 80% of them occurred in children under one year of age. Among those who died up to one year of age, most of them had low birth weight, being children of young mothers and with incomplete high school education. Conclusion: it is essential to combat the regional disparities that interfere in childhood mortality, after all the characteristics and predominance of avoidable mortality seems to indicate the weaknesses in the health care of the mother-child binomial.